Loss-of-consciousness: sources of GABAergic input to the mesopontine tegmental anesthesia area - Ibraheem, Angham; Vaso, Kristina; Minert, Anne; Yatziv, Shai-Lee; Baron, Mark; Devor, Marshall (Frontiers in Neuroscience, 2025)
Exposure of neurons in the brainstem mesopontine tegmental anesthesia area (MPTA) to minute quantities of GABAergic general anesthetics at clinically relevant concentrations is sufficient to induce loss-of-consciousness (LOC), while lesioning this nucleus renders rodents relatively insensitive to these anesthetics delivered systemically. The MPTA thus appears to be a key GABA-receptive target in brain mechanisms of clinical anesthesia. As lesioning the MPTA also affects natural instances of LOC including sleep and fainting, it is of interest to know the source(s) of endogenous GABA present in the MPTA. Here, we used retrograde tracing combined with immunolabeling to locate GABAergic neurons that provide the MPTA with synaptic input. Sources of glycinergic and glutamatergic input were also explored. Abundant GABAergic neurons with axonal projections to the MPTA were found in: (1) deep laminae of the neocortex rostrally, (2) a mesolimbic field ranging from the basal forebrain to the limbic midbrain, and (3) deep cerebellar nuclei and the rostroventromedial medulla (RVM). All three showed ipsilateral predominance. Only modest numbers of glycinergic input neurons were found, mostly in the hindbrain. Glutamatergic sources of MPTA input were mainly in the cortex, the ventral tegmental area and the RVM. The endogenous modulatory input to the MPTA identified here, particularly the GABAergic input, likely plays a significant role in the various natural circumstances that involve LOC. GABAergic anesthetics, in turn, agents that permit pain-free surgery, appear to act by substituting for endogenous GABA in the MPTA and hence co-opting endogenous GABA-receptive brain circuitry related to consciousness and its loss.